Elementos de vulnerabilidade programática em saúde segundo os níveis de atenção em cidades rurais - Araújo, Eunice Aristides (2017)
This current study aimed to analyze elements of programmatic vulnerability in health from the perception of residents living in rural cities of Paraiba, according to the level of care. Those cities are characterized by to present low economic, social, demographic levels, with population less than 10,000 inhabitants. The precariousness in the coverage, organization, structure and access to health services are important elements of programmatic vulnerability that make the populations of these municipalities more vulnerable to illness and / or disease aggravation, as well as interfering in the organization of health care networks. Participated these study 992 subjects, distributed among 31 municipalities of the state. To collect the data, the questionnaire "Health care and vulnerability assessment" was analyzed using the SPSS Software for Windows (SPSS) version 20.0. The sample consisted of participants, mostly women (74%), married (70%), of productive age (M = 43.6 years, DP = 14.8), ranging from 21 to 85 years. With regard to the search for care and level of care, it was found that 41% of the sample sought early care services, 12% appointment with specialist doctors, 12% prevention and 8% prenatal care. In order to treat their health problems, 32% participants were cared for in basic care (ESF), 24% in medium complexity services (UPA / Polyclinic) and 44% in high complexity (hospitals). To identify the evaluation of the health services team and structure among the macro-regions (João Pessoa, Campina Grande, Patos and Sousa), users responded to two items whose responses were scalar ranging from 0 to 10. The result pointed to a regular evaluation, with an average of 7.44 (DP = 2.48) for the health professionals and 6.93 (DP=2.73) for the physical and organizational structure of the health service. In the macro-regions of health, a statistically significant difference was found between the evaluative averages (p =.03) only between Campina Grande (M = 6.71; SD = 2.85) and Sousa (M = 7.43; SD = 2.50) regarding the structure and organization of the service, with a more positive evaluation for the latter. In order to verify the perception of the inhabitants of rural cities about the health services, four aspects were evaluated: organization, bond and reception, resolution and prevention. Considering the evaluative factors related to health macro-regions, there were positive evaluations with some variability in indices, however, only the Prevention factor presented a statistically significant difference (f = 6.921; p = 0.000). In general terms, the data of this study allow to conclude that the precariousness in the structure and organization of the services available in the rural cities interfere in the search and level of care, contributing to the disarticulation in the health attention networks such as the overcrowding in the services of high complexity and emptying in the basic care.